INVESTING AND PROTECTION OF INVESTOR IN STOCK MARKET - Manurung, Adler Haymans (Indonesian Journal of International Law, 2021)
This paper discusses three areas, namely investment, investors’ characteristics, and a place of investment, which is stock market. In investing in stock market, investors need to utilize funds which are not currently used so they would not worry about the decrease value that may occur in a short term. Investors need to understand the risks which can be tolerated to invest. On the other hand, investors must be protected to prevent inappropriate transactions. Regulators must endorse rules regularly revised to suit the existing condition that can satisfy many parties.